Sigma receptors and mitochondria-associated ER membranes are converging therapeutic targets for Alzheimer’s disease - Lotlikar, Madhura S.; Zellmer, Jacob C.; Bhattacharyya, Raja (Frontiers in Neuroscience, 2025)
Alzheimer’s disease (AD) begins decades before clinical symptoms emerge. The “amyloid hypothesis” suggests that amyloid-β (Aβ) deposition initiates a cascade of tau hyperphosphorylation, neuroinflammation, and neuronal loss leading to cognitive decline. The recent success of anti-Aβ therapies such as Leqembi in prodromal or mild cognitive impaired patients underscores the importance of early intervention and Aβ clearance. However, safety and cost limitations highlight the need for alternative therapeutic strategies. Small-molecule modulators of Sigma-1 and Sigma-2 receptors (σ1R and σ2R) have emerged as promising candidates for AD treatment. σ1R agonists exhibit neuroprotective and anti-amnestic effects under pathological conditions without affecting normal cognition. Beyond AD, σ1R is implicated in several neurodegenerative diseases including ALS (amyotrophic lateral sclerosis), Parkinson’s, and Huntington’s diseases, stroke, and epilepsy. σ1R plays a key role at mitochondria-associated ER membranes (MAMs)—specialized lipid raft-like domains that form functional membrane contact sites between the endoplasmic reticulum (ER) and mitochondria. β-secretase (BACE1), γ-secretase, and their substrates APP and palmitoylated APP (palAPP) localize in the MAMs, promoting amyloidogenic Aβ production. MAMs serve as dynamic hubs for inter-organelle communication, calcium signaling, and lipid metabolism. The “MAM hypothesis” proposes that MAM dysregulation drives early AD pathology and persists throughout disease progression, contributing to neurofibrillary tangle formation, calcium imbalance, and neuroinflammation. This review aims to summarize the current understanding of σ1R-mediated regulation of MAMs and its neuroprotective mechanisms, highlighting potential therapeutic opportunities for targeting σ1R in AD and other neurodegenerative disorders.